BUSINESS TENURE, OPERATING HOURS, AND COMPETITORS: EFFECTS ON CUSTOMERS AND FINANCIAL IMPLICATIONS - Prayogi, Oki; Hasanah, Uswatun; Manalu, Royen Rivaldo; Situmorang, Rio; Lubis, Evi; Manik, Kristina (Bisma: Jurnal Bisnis dan Manajemen, 2025)
This study aims to examine the effect of business tenure, operating hours, and the number of competitors on the number of customers for street vendors in Medan, along with the financial implications of customer traffic. Using a quantitative approach with a case study method, data were collected through structured questionnaires, involving direct numerical input provided by street vendors. The research was conducted in selected districts of Medan using purposive sampling, with a total sample of 30 respondents. The data were analyzed using multiple linear regression. The findings indicate that, collectively, business tenure, operating hours, and the number of competitors significantly affect customer volume. However, on an individual basis, only operating hours had a statistically significant impact, suggesting that longer operating hours are positively associated with attracting more customers. In contrast, business tenure and competition did not show a meaningful influence. The regression model met the assumptions of normality and showed no signs of heteroscedasticity. From a financial perspective, the results imply that optimizing daily operating hours may enhance customer reach and, subsequently, improve income potential, whereas simply having longer business experience or facing more competitors does not necessarily guarantee higher earnings.